LIMNOLOGY OF TWO UNMANAGED URBAN AND PERI URBAN PONDS OF CHHATTISGARH IN RELATION TO FISH CULTURE - ROY, KOUSHIK (Journal of the Inland Fisheries Society of India, 2021)
Seasonal dynamics of physico-chemical parameters, dissolved nutrients, primary productivity and plankton population were investigated in two unmanaged urban and peri urban ponds, located in Raipur district of Chhattisgarh with special reference to fish culture during April 2013 to March 2014. The samples were collected and analysed at monthly intervals. Nutrient - wise, the peri urban pond had greater fertility than the urban pond. The urban pond was mesotrophic in nature while the peri urban pond showed signs of progressive eutrophication as evident from the primary productivity and plankton population.Most of the physico - chemical parameters reached their peak during the winter months and were within the optimum range for fish culture throughout the year. It was concluded that the present extensive fish culture practices in these water bodies should be upgraded to semi intensive for their proper utilization and maximizing fisheries production. Key words: Ponds, physico-chemical parameters, dissolved nutrients, primary productivity, plankton, Chhattisgarh.